PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS VIII SMP KARTIKATAMA METRO TAHUN PELAJARAN 2017/2018 - Aprilia, Nia; Partono, Partono; Alarifin, Dedy Hidayatullah; Prihandono, Eko (JURNAL FIRNAS, 2021)
Abstract: Efforts to improve the activities and learning outcomes of junior highschool students Kartikatama Metro so far the school and teachers have done a lotof effort, but in fact science learning in junior Kartikatama Metro there are still manydifficulties. Therefore, a research entitled Implementation of Quantum TeachingLearning Model to Increase Student Activity and Learning Outcomes of Class VIIISMP Kartikatama Metro Lesson Year 2017/2018. The purpose of this study is toimprove the activity and learning outcomes of students with the application ofquantum teaching models in grade VIII SMP Kartikatama Metro Lesson year2017/2018. The research type is Classroom Action Research (PTK), with researchdesign using four cycles of action consisting of, planning, implementation,observation, and reflexology. The subject of this research is the students of classVIIIA. The research instrument uses an observation sheet to obtain data of studentlearning activities and test questions to obtain student learning result data. Basedon the result of research on the application of learning quantum teaching model,the achievement level of learning activity of cycle I is 60,50% and cycle II is72,84%, and the percentage of active students in cycle I is 31,67%, then increaseon cycle II by 95%. Furthermore, for the learning outcomes in the cycle I learnedstudent completeness reached 56.67% (high enough), increased in cycle II to86.67% (very high). Based on the result, it can be concluded that the application ofquantum teaching model can increase the activity and learning outcomes ofstudents in SMP Kartikatama metro Lesson Year 2017/2018.Keywords: Quantum teaching learning model, student learning activity, studentlearning outcomes